2011
DOI: 10.2478/s11535-010-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solvent extraction on antioxidant properties of apricot fruit

Abstract: Two solvent extraction procedures were used to investigate the extraction efficiency in terms of total antioxidant capacity and\ud total phenols in apricot fruit. Samples were either sequentially extracted with aqueous ethanol (ethanol/water 80% v/v) and\ud tetrahydrofuran or directly extracted with tetrahydrofuran. Each extract was analyzed for total antioxidant capacity by the\ud Trolox Equivalent Antioxidant Capacity (TEAC) assay and total phenols by the Folin-Ciocalteu assay. The results showed\ud that usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
2
19
1
Order By: Relevance
“…linear correlation between the values of phenolic content and antioxidant activity [25]. The difference in morpho-anatomical structure and physiological activity of different plant parts contribute to varying phenolic content and antioxidative activity values.…”
Section: Resultsmentioning
confidence: 97%
“…linear correlation between the values of phenolic content and antioxidant activity [25]. The difference in morpho-anatomical structure and physiological activity of different plant parts contribute to varying phenolic content and antioxidative activity values.…”
Section: Resultsmentioning
confidence: 97%
“…The study by Scalzo et al [5] found no correlation between antioxidant capacity and phenolic content whereas the opposite was found by Drogoudi et al [12]. A strong [26], nectarines, peaches and plum was reported [29].…”
Section: Antioxidant Capacitymentioning
confidence: 93%
“…Higher ferric reducing antioxidant potential with acetone suggests that apricot kernel contains significantly higher lipophilic than hydrophilic antioxidants. Higher lipophilic antioxidants in kernel in contrast to apricot fruit [5,26] could be due to higher phenolic content in kernel oil. Similar results have been reported in embryo extracts of Melicoccus bijugatus Jacq.…”
Section: Antioxidant Capacitymentioning
confidence: 98%
“…Prior to the determination of the antioxidant activity and total phenolics content, the optimum conditions for extraction methods of the antioxidants are needed. Some typical solvents have been used for the extraction of antioxidants including methanol, ethanol, acetone, water, acetonitrile, tetrahydrofuran, hexane, ethyl acetate (Leccese et al 2011;Sang et al 2014;Nguyen et al 2015). A large number of extraction techniques for the antioxidants have also been developed for analysis of the antioxidants including ultrasound assisted extraction (UAE), microwave assisted extraction (MAE), supercritical fluid extraction (SFE), pressurized fluid extraction (PFE), accelerated solvent extraction (ASE) and enzyme assisted extraction (Chen et al 2015;Ranic et al 2014).…”
Section: Introductionmentioning
confidence: 99%